Freedom's Ferment : Phases of American Social History to 1860 - Tyler, Alice Felt, 1892- (Book collections on Project MUSE., 1944)
In this historical synthesis of men and movements, Alice Felt Tyler shows in action the democratic faith of the young American republic. She tells the stories of the reform movements and social and religious experiments characteristic of the early half of.